Waste Skin of Hawaiian Ladyfish (Elops hawaiensis) Utilization as Gelatin Raw Material With Immersion Solution Combination - Devi Faustine Elvina Nuryadin; Sakinah Haryati; Indra Taruna Widodo; Aris Munandar; Dini Surilayani; Ginanjar Pratama; Afifah Nurazizatul Hasanah (Food ScienTech Journal, 2022)
Bontot from Domas Village, Pontang District, Serang Regency is a fish jelly product. The manufacture of Bontot produces fish skin waste with a percentage of 10% of the whole weight of the fish. This waste can be reduced by applying the concept of zero waste in the processing of bontot which is reused as a raw material in the manufacture of gelatin. This research aims to determine the best NaOH concentration in the manufacture of gelatin from the skin of Hawaiian ladyfish (Elops hawaiensis) and to determine the effect of NaOH immersion on the organoleptic, chemical, and physical qualities of the gelatin. This study used an alkaline solution (NaOH) with a concentration of 0.1%; 0.3%; and 0.5%, which is then followed by a 6% acid solution immersion process. The production of gelatin from the skin of Hawaiian ladyfish was carried out using a one-factor completely randomized design (CRD) with 2 replications (duplo) accompanied by non-parametric analysis which was carried out for organoleptic testing with a hedonic scale using the Kruskal Wallis test. The results showed that the best combination was 0.1% NaOH and 6% HCl with a hedonic value of 3.7 with a whitish-yellow color; odor hedonic value 3.13; 11% yield; gel strength 280.43 g bloom; viscosity 36.95 cP; water content 8.75%; ash content 0.58%; and a pH value of 6.88